Evidence of band filling in PbS colloidal quantum dot square superstructures. Issue 33 (10th August 2021) - Liu, Liming; Septianto, Ricky Dwi; Bisri, Satria Zulkarnaen; Ishida, Yasuhiro; Aida, Takuzo; Iwasa, Yoshihiro
Abstract : Electric-double-layer transistor and spectroelectrochemical measurements reveal the filling of the degenerated conduction level of the PbS quantum dot square superstructures. Abstract : PbS square superstructures are formed by the oriented assembly of PbS quantum dots (QDs), reflecting the facet structures of each QD. In the square assembly, the quantum dots are highly oriented, in sharp contrast to the conventional hexagonal QD assemblies, in which the orientation of QDs is highly disordered, and each QD is connected through ligand molecules. Here, we measured the transport properties of the oriented assembly of PbS square superstructures. The combined electrochemical doping studies by electric double layer transistor (EDLT) and spectroelectrochemistry showed that more than fourteen electrons per quantum dot are introduced. Furthermore, we proved that the lowest conduction band is formed by the quasi-fourth degenerate quantized (1Se ) level in the PbS QD square superstructures.